2006
DOI: 10.1289/ehp.9478
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to Environmental Toxicants and Attention Deficit Hyperactivity Disorder in U.S. Children

Abstract: ObjectiveThe purpose of this study was to examine the association of exposures to tobacco smoke and environmental lead with attention deficit hyperactivity disorder (ADHD).MethodsData were obtained from the National Health and Nutrition Examination Survey 1999–2002. Prenatal and postnatal tobacco exposure was based on parent report; lead exposure was measured using blood lead concentration. ADHD was defined as having current stimulant medication use and parent report of ADHD diagnosed by a doctor or health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
333
7
18

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 499 publications
(383 citation statements)
references
References 53 publications
25
333
7
18
Order By: Relevance
“…Lead quantities formerly regarded as trivial are associated with permanent cognitive damage in children [3], including those prenatally exposed [4]. Lead is associated with impaired motor function [5], attentional dysfunction [6], and even criminal behavior [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lead quantities formerly regarded as trivial are associated with permanent cognitive damage in children [3], including those prenatally exposed [4]. Lead is associated with impaired motor function [5], attentional dysfunction [6], and even criminal behavior [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the analysis from the National Health and Nutrition Examination Sur vey on 4704 children aged 4-15 years indicated the preva lence of parent-reported ADHD diagnosis or treatment four times higher among children with the blood lead level > 2.0 μg/dl, compared with those with the blood lead level < 0.8 μg/dl (OR = 4.1; 95% CI: 1.2-10.0) [6]. The later analysis conducted as part of the same survey (on 2588 children at 8-15 years of age) indicated that children who were exposed to prenatal tobacco and lead had greater risk of ADHD than it would be expected if the indepen dent risk was multiplied (OR = 8.1; 95% CI: 3.5-18.7; to bacco -lead exposure interaction p < 0.001) [51].…”
Section: Summary Of the Study Resultsmentioning
confidence: 99%
“…If further research reveals that the latter is more likely, our study raises concerns that obese children may be susceptible to adverse neurodevelopmental and respiratory effects that have been associated with BPA exposure in children. 5,6 …”
Section: Bisphenol a And Obesity In Children And Adolescentsmentioning
confidence: 99%
“…The latter group of patients showed the largest benefit by biomarker-guided treatment in a previous study. 5 Adding novel management strategies in patients for whom the physician already knows best is not necessary. Such strategies may be needed for patients when the physician's assessment fails.…”
Section: Conflict Of Interest Disclosuresmentioning
confidence: 99%